2019
DOI: 10.3390/met9090958
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Mechanical Properties of a Hot Rolled High-Strength Steel Produced by Ultra-Fast Cooling and Q&P Process

Abstract: The quenching and partitioning (Q&P) process of advanced high strength steels results in a significant enhancement in their strength and ductility. The development of controlled rolling and cooling technology provides an efficient tool for microstructural design in steels. This approach allows to control phase transformations in order to generate the desired microstructure in steel and, thus, to achieve the required properties. To refine grain structure in a Fe-Si-Mn-Nb steel and to generate the microstructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…During further rapid cooling below the martensite start temperature, the deformed austenite transformed into martensite. Due to the effect of deformation in austenite and the very high cooling rate, martensite is formed with very fine martensite blocks and a large amount of retained austenite [31][32][33][34][35][36][37]. Other researchers [38,39] have also reported that the ratio of martensite to austenite depends a lot on laser power, scan speed, hatching pitch, and layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…During further rapid cooling below the martensite start temperature, the deformed austenite transformed into martensite. Due to the effect of deformation in austenite and the very high cooling rate, martensite is formed with very fine martensite blocks and a large amount of retained austenite [31][32][33][34][35][36][37]. Other researchers [38,39] have also reported that the ratio of martensite to austenite depends a lot on laser power, scan speed, hatching pitch, and layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the DQ&P process refined retained austenite, promoting the TRIP effect and toughness of the grade, in comparison to the alloy without Q&P treatment. The process proposed by Kantanen et al in [5] was designed for the industrial hot strip production of Fe-0.3C-2.0Mn-0.6Si-1.1Al-2.2Cr and Fe-03C-1.9Mn-1.0Si-1.0Cr (wt.%) steels. The positive effect of DQ&P on the volume fraction of retained austenite, tensile mechanical behaviour, and impact toughness was shown.…”
Section: Contributionsmentioning
confidence: 99%
“…The process of steel quenching is one of the physically most complicated engineering processes which involves many physical processes, such as microstructure transformations, heat exchange, heat transfer and heat conduction, generation of distortion and residual stresses and crack formation [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%